(untitled) (Impetus, 2021)
Introduction. Injuries have been an inherent aspect of sports practice, where it is possible to show the appearance of these when performing poorly in certain movements or the overuse of some muscle groups in sports gestures. Aim. Know the main lower limb injuries in the Santo Tomás University soccer team, caused by external causes. Materials and methods. Descriptive cross-sectional study, the chosen population was the players of the Santo Tomás University soccer team. For data collection, a survey was designed that was carried out with criterion validity through expert judgment and its reliability was measured by correlation coefficient in a test-retest that resulted in a value of 0.95. Results. 83.3% of the population has suffered an injury during sports practice; of these, 53.3% have had between 1 to 2 injuries. Discussion and Conclusions. There is a high percentage of presence in sports injuries in soccer players, this leads to the individual being outside the field of play for a time and lowering their physical condition, which in the long term affects the entire team and in the The medium-term affects your health that is often irreversible, although the reported results are related to what was found in other studies, even these risk factors are not taken into account in the training processes.